Smart device that helps parents and teachers create discipline in children with ADHD - Barboza-Artavia, Alexa (2024)
Getting a 5-12 year old child to have good habits and be disciplined in their schoolwork requires mainly constancy and perseverance, but for children with attention deficit hyperactivity disorder (ADHD), this translates into a great challenge and represents a constant struggle during their learning process. From their young age, children with ADHD suffer in silence from self-esteem problems and their mental health is affected by not understanding why they are different from others, which is why the support of parents and teachers is essential to avoid these scenarios, however, they have a major limitation, since, at present, there are no technological and accessible tools to help them achieve this goal. To address this need, an innovative solution was developed based on the user-centered design methodology which emphasizes the importance of taking into account at all stages of design, the needs and limitations of the user, in order to obtain an efficient product that provides a real solution. In this project, developed in the field of industrial design, the result was Pandi, a gadget that seeks to help parents and teachers to create discipline in children with ADHD through a virtual friend that works in turn as an educational tool contributing to the change of lifestyle of this population so vulnerable to school failure.